Volunteering, Income Support Programs and Persons with Disabilities - Campolieti, Michele; Gomez, Rafael; Gunderson, Morley (Relations industrielles / Industrial Relations, 2009)
We study the propensity of persons with disabilities to engage in volunteer activity using the Participation and Activity Limitation Survey (PALS). Our principal focus is on the effects of various income support programs on persons with disabilities participation in volunteer activities because income support programs can differ with respect to their treatment of unpaid work. For example, workers’ compensation programs embody strong disincentives to volunteering while public disability insurance programs explicitly encourage unpaid work. We find that workers’ compensation is associated with decreases in the probability of volunteering while public disability insurance is associated with increases in the propensity to volunteer. The relevance of these results to both theories of volunteerism and public policy is discussed.